USER INTERFACE DESIGN FOR A HEALTH SERVICE AT PT UNITED TRACTORS - Reswara, R. Alfiarto Randi (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 5 No 1 (2024): JITTER, Vol.5, No.1, April 2024, 2024)
The EHS Department is one of the departments in PT United Tractors. The task of the EHS Department is to support the performance of employees working at PT United Tractors. One form of support provided by this department is health services for employees. To provide the best experience in supporting employee performance activities, the EHS Department has an idea to create a platform that is able to handle all activities to support employees in terms of health. The program is named "Hi Doctor". This program will later have features that make it easier for employees to access of health services at PT United Tractors. The stages of working on this application begin with designing UI / UX Design, this task was carried out by the author and his team during the internship. The method used in the UI/UX Design work is Design Thinking, Design Thinking is used as a method in designing the "Hi Doctor" application design. The Design Thinking method is a human-centered approach to solving problems and bringing about new innovations. The results of this study are application prototypes with UI/UX designs that have been developed and adapted to the problems and needs found. The use of the Design Thinking method will present a solution that meets the needs and can solve user problems when using the "Hi Doctor" application.